Discovery of Major Basement‐Cored Uplifts in the Northern Galiuro Mountains, Southeastern Arizona: Implications for Regional Laramide Deformation Style and Structural Evolution. Issue 10 (23rd October 2018) - Favorito, Daniel A.; Seedorff, Eric
Abstract: The Laramide orogeny is poorly understood in southeastern Arizona, largely because of complex structural overprinting by mid‐Cenozoic extension that occurred over large areas. This study integrates new geological mapping with previous work, combined with structural reconstructions and forward modeling, to determine the primary structural style, timing, evolution, and kinematics of Laramide shortening in the northern Galiuro Mountains. Cenozoic normal faulting in the study area is minor and has only resulted in up to 13° of eastward tilting, as indicated by the gentle dips of synextensional strata. Detailed mapping has revealed newly identified reverse fault systems measuring at least 50 km in combined strike length. Each major fault strikes north‐northwest, dips moderately to the west, places older rocks on younger, and has related fault‐propagation folds. Once restored to their original orientation, reverse faults range in dip from 38° to 47°. These moderate dips of faults combined with related folds, the significant degree of basement involvement, and cover sequence lacking obvious penetrative deformation indicate that these faults are thick‐skinned, basement‐cored uplifts. Forward modeling and Cenozoic erosion surfaces suggest regionally extensive Laramide‐age tilting to the west‐southwest and gentle folding, possibly caused by a regional‐scale reverse fault underlying the study area. These results are consistent with the interpretation that Laramide shortening in southeastern Arizona was primarily characterized by thick‐skinned tectonics. Kinematic indicators, folded basement rocks, north‐northwest strikes of reverse faults, and lack of evidence for basin inversion suggest that preexisting basement faults and fabrics had little or no effect on the subsequent structural evolution. Plain Language Summary: The Late Cretaceous to early Eocene Laramide orogeny was a period of crustal shortening in the North American Cordillera that involved two different styles of reverse faulting. One style involves low‐angle thrusts that typically slip parallel to bedding planes in layered rocks, whereas the other style involves faults that cut across bedding at moderate angles and continue downward through underlying crystalline basement rock. In southeastern Arizona, the style of Laramide shortening is debated and not well understood, in part because most of the region has undergone subsequent Cenozoic extension that has significantly rotated, dismembered, and buried most faults formed during Laramide crustal shortening. This study examines a newly discovered set of Laramide reverse faults that extend for more than 50 km along strike and that have only been affected by minor extension. Results from field mapping and structural modeling indicate that these faults are basement‐involved, moderate‐angle reverse faults. Because the upper crustal architecture across the region is largely consistent, the region as a whole may be characterized by moderate‐angle reverse faults. Thus, nearby Laramide faults that have been previously interpreted as low‐angle thrusts deserve reexamination. Key Points: Laramide reverse faults measuring at least 50 km in combined strike length were discovered Moderate restored dip of reverse faults, fault‐propagation folds, and high degree of basement involvement indicate thick‐skinned shortening Stratigraphic and structural data suggest that arching related to a regional‐scale reverse fault tilted the area during the Laramide